Compliance costs of environmental regulation with incomplete information. Application to fixed sources of PCE in Santiago, Chile - Clerger, Gaspard (Estudios de Economía, 2016)
We study the cost-effectiveness of a transferable emissions permit system (TEPS)vis a vis a system of emissions standards. Our analysis includes along withabatement costs, the costs of enforcing the system to induce compliance. Further,the analysis considers complete and incomplete information. The numericalsimulations are performed for the case of fixed sources operating under theEmissions Compensation Program (ECP) in Santiago, Chile. The results suggestthat a TEPS is not able to induce compliance at minimum enforcement costs, butthis regulatory system allow the regulator to achieve the environmental targetwith minimum aggregate compliance costs.